Anaylysis of the stories "Muz Kongil" and "Yol" by Sotim Avaz (Eurasian Journal of Learning and Academic Teaching, 2023)
This article analyzes the stories "Muz Kongil" and "Yol" composed by Sotim Avaz, a child of the Khorezm individuals, additionally talks almost the pith of the story, composing aptitudes, and characters.